Effect of blending on physicochemical properties of groundnut, palm, and sunflower oil blends: EFFECT OF BLENDING ON PHYSICOCHEMICAL PROPERTIES OF GROUNDNUT, PALM, SUNFLOWER OIL - PREETI BAJPAI; RENU MOGRA (Journal of Oilseeds Research, 2023)
The composition of the diet plays an important role in the management of lipid and lipoprotein concentrations in the blood. Vegetable oil plays a vital role in determining the human health due to its fatty acid composition. High intakes of saturated fatty acids (SFA) increase blood levels of total and low-density lipoprotein cholesterol (LDL-C) and accelerate the process of atherosclerosis. On the other hand, monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) have the opposite effects. According to WHO and other health agencies, nutritionally superior oil must fall in the ratio of 1:1-3:1; SFA, MUFA and PUFA, respectively, however evidences suggest that no single oil can provide the recommended dietary fat ratio. To combat this fatty acid ratio problem, blending of vegetable oils is gaining popularity in the oil industry to satisfy consumer needs. Present investigation was carried out with the objective of evaluating the effect of blending on physicochemical properties of groundnut, palm and sunflower oil blends. The physicochemical properties like specific gravity, refractive index,smoke point, moisture, and free fatty acid value, peroxide value, saponification value and iodine value of vegetable oils and its blend in ratio of 50:25:25 of groundnut oil, palm oil and sunflower oil respectively were evaluated using standard analysis methods. It was observed that blending of groundnut oil with palm oil and sunflower oil affected and improved the physicochemical properties of the oil blend.